2016
DOI: 10.15384/kjhp.2016.16.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Status in Korean Adult Population in Relation with Socioeconomic and Medical Factors

Abstract: Background: Influenza causes morbidity and mortality, resulting in the medical and socioeconomic costs. We aimed to analyse whether socioeconomic and medical factors may affect influenza vaccination status divided into 2 groups; one aged 19 to 64 years old and the other aged 65 or over who are eligible for free vaccination. Methods: The study included 1,412 individuals aged 19 and over who responded to influenza vaccination survey, based on 2013 National Health and Nutrition Examination Survey. Related factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…14,19 However, the majority of studies, which included education level as a variable in multivariate analyses did not show significant correlations with influenza vaccination. 9,11,14,15,18,19 Income was not a significant factor for influenza vaccination in this study, and many other studies supported these findings based on inconsistent results. 9,11,15,16,18,19 However, Lee et al…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…14,19 However, the majority of studies, which included education level as a variable in multivariate analyses did not show significant correlations with influenza vaccination. 9,11,14,15,18,19 Income was not a significant factor for influenza vaccination in this study, and many other studies supported these findings based on inconsistent results. 9,11,15,16,18,19 However, Lee et al…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, many previous studies have also reported a positive association between increasing age and influenza vaccination uptake. 9,11,12,[14][15][16]18,19 In this study, a higher level of education was associated with a lower vaccination rate. This result was supported by previous studies in South Korea which showed similar results following bivariate analyses.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations